Sensory and cognitive event-related potentials in myalgic encephalomyelitis. Issue 3 (March 1990) - Prasher, D; Smith, A; Findley, L
Abstract : Myalgic Encephalomyelitis (ME) is a form of post viral fatigue syndrome resulting in myalgia and fluctuating fatiguability. Symptoms reflecting central nervous system dysfunction are common and include muscle weakness, headache, sensory disturbances, poor short term memory and impairment of concentration. In view of the fact that sensory and cognitive disturbances are experienced by many patients objective evidence was sought with multi-modality sensory evoked potentials and auditory event-related cognitive potentials in a group of ME patients both with and without the enteroviral antigen, VP1 test positive. The auditory brainstem, median nerve somatosensory and pattern reversal checkerboard visual potentials were normal for all 37 patients tested. In contrast to the sensory potentials significant differences in the mean latencies of the cognitive potential N2 and P3 were found. Reaction times were also significantly prolonged but the performance in terms of error was not significantly affected. No significant difference emerged in any of the parameters for the VP1 test. P3 was abnormal in latency or amplitude in 36% of the VP1 positive patients for the frequency discrimination task and 48% for the more difficult duration discrimination task. The abnormalities indicate attentional deficits in some patients and slower speed of information processing in others. The prolonged latencies observed in these patients have not been observed in patients with depression in many other studies.